A Design Method for Rail Profiles in Switch Panel of Turnout Based on the Contact Stress Analysis. (9th October 2020) - Chen, Dilai; Shen, Gang; Mao, Xin; Chen, Buchen
Abstract : Contact stress between wheel and rail is believed to cause damage to the rail. The relationship between the contact stress and the radius of the rail is initially based on the Hertz contact theory. By adjusting its radius, the rail profile is designed with an objective of reducing the maximal contact stress between wheel and rail. The rail profile of turnout is parameterized by defining several control cross sections along the switch. The experiment of dynamic vehicle-turnout interaction is also carried out to investigate the effect of the improved rail profile on the dynamical behavior of the vehicle. The method is then verified through examples using rail profile with a switch width of 20 mm and LM worn-type tread at the CN60-350-1:12 turnout. The results show that the designed rail has a higher matching degree with the wheel profile. It can reduce the contact stress, improve the wheel-rail contact state, and prolong the service life of the rail without deteriorating the dynamic performance of the vehicle passing through the turnout.